Analisis Chat GPT atas Peran Neuroaesthtetics dalam Teater - Yogie Pranowo (Universitas Katolik Parahyangan, 2023)
Appreciating a work of art, particularly in theater performances, often leaves humans overwhelmed with indescribable emotions. This is due to the role of empathy within human beings that relates to what is seen on stage. In theoretical studies, art can be enjoyed through phenomenological aspects and more empirical approaches. One of them is through the lens of neuroaesthetics. This article employs a qualitative descriptive approach using the ChatGPT AI. The conclusion is that the relationship between aesthetic experiences and brain function ultimately reinforces each other.